Drilling Technology 2021
DOI: 10.5772/intechopen.96497
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Performance of Drilling Operations for Improving Productivity

Abstract: Drilling is a vital machining process for many industries. Automotive and aerospace industries are among those industries which produce millions of holes where productivity, quality, and precision of drilled holes plays a vital role in their success. Therefore, a proper selection of machine tools and equipment, cutting tools and parameters is detrimental in achieving the required dimensional accuracy and surface roughness. This subsequently helps industries achieving success and improving the service life of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For instance, AA2024-T3 is installed in aircraft fuselage skins due to its high fatigue resistance [2]. Furthermore, in the aerospace industry, the drilling process is used to assemble different structures, and thus a large number of holes are required for installing rivets and bolts [3][4][5]. Poor hole quality can lead to part rejections in quality control.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AA2024-T3 is installed in aircraft fuselage skins due to its high fatigue resistance [2]. Furthermore, in the aerospace industry, the drilling process is used to assemble different structures, and thus a large number of holes are required for installing rivets and bolts [3][4][5]. Poor hole quality can lead to part rejections in quality control.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature suggests that MDMT is a promising approach for improving the efficiency and accuracy of drilling processes [10]. However, further research is needed to fully understand this approach's capabilities and limitations and develop new techniques and tools to enhance its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…These include developments of new methods in production methods and systems and optimization for improving productivity or maximizing profit. For example, drilling as the most used production process is still the subject of study for improvement by contemporary researchers, and many of these works can be found in the literature [1][2][3][4][5][6][7][8]. There are also reports on the improvements of conventional and nonconventional production processes [9][10][11], optimization of processes [6,12,13], and enhancement of properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, drilling as the most used production process is still the subject of study for improvement by contemporary researchers, and many of these works can be found in the literature [1][2][3][4][5][6][7][8]. There are also reports on the improvements of conventional and nonconventional production processes [9][10][11], optimization of processes [6,12,13], and enhancement of properties [14]. In addition, there are many reports in the literature on the development of production systems including quality control, process planning, and production planning and control systems [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%